2020
DOI: 10.1002/cncr.32770
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic potential of liquid biopsy tracking in the posttreatment surveillance of patients with nonmetastatic nasopharyngeal carcinoma

Abstract: BACKGROUND:The current study was performed to investigate whether circulating cell-free Epstein-Barr virus DNA (cfEBV DNA) would be useful for posttreatment surveillance in patients with nasopharyngeal carcinoma (NPC). METHODS: The authors identified a total of 1984 nondisseminated NPC patients from an institutional big-data research platform. Blood samples were collected within 3 months of the completion of radiotherapy and every 3 to 12 months thereafter for cfEBV DNA analysis. Patients were followed until d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 25 publications
4
27
0
Order By: Relevance
“…The patients of Pattern 5 had the worst prognosis on progression, metastasis, recurrence and mortality, and the patients of Pattern 1 had the best prognosis. This conclusion was similar to other studies [30,31]. As to pattern 2 and pattern 3, the patients of pattern 2 had a better prognosis than those of pattern 3, consistent with Qu's meta-analysis that post-treatment EBV DNA level had greater impact than pretreatment EBV DNA on clinical outcomes of NPC [19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The patients of Pattern 5 had the worst prognosis on progression, metastasis, recurrence and mortality, and the patients of Pattern 1 had the best prognosis. This conclusion was similar to other studies [30,31]. As to pattern 2 and pattern 3, the patients of pattern 2 had a better prognosis than those of pattern 3, consistent with Qu's meta-analysis that post-treatment EBV DNA level had greater impact than pretreatment EBV DNA on clinical outcomes of NPC [19].…”
Section: Discussionsupporting
confidence: 91%
“…In daily clinical practice, it is very important to early detect locoregional tumor recurrence post-treatment, because timely salvage treatment could improve survival outcome of these patients [32]. Chen's ndings showed that positive cell free EBV DNA results preceded radiological and/or clinical evidence of disease recurrence by a median of 2.3 months [31]. These ndings con rmed that plasma EBV DNA was a signi cant sensitive and non-invasive predictor of tumor recurrence.…”
Section: Discussionmentioning
confidence: 88%
“…This conclusion was similar to other studies. 34,35 As to pattern 2 and pattern 3, the patients of pattern 2 had a better prognosis than those of pattern 3, consistent with Qu's meta-analysis that posttreatment EBV DNA level had greater impact than pretreatment EBV DNA on clinical outcomes of NPC. 19 Moreover, the patients of pattern 4 had a worse prognosis than those of pattern 2 and 3, the possible explanation was that these patients had a higher baseline and residual tumor load.…”
Section: Discussionsupporting
confidence: 65%
“…36 Chen's findings showed that positive cell free EBV DNA results preceded radiological and/or clinical evidence of disease recurrence by a median of 2.3 months. 35 These findings confirmed that plasma EBV DNA was a significant sensitive and noninvasive predictor of tumor recurrence. Based on our results, we suggested a long-term follow-up program according to dynamic changes in plasma EBV DNA.…”
Section: Discussionsupporting
confidence: 62%
“…Recent emphasis has also focused on posttreatment EBV DNA as prognosticators (6,10,11,15,19,20,(26)(27)(28). Chen et al, in their recent study, further demonstrated the role of plasma EBV DNA in the detection of early disease recurrence among patients with NPC after treatment (29). Leung et al showed that detectable plasma EBV DNA titers at completion of 4 weeks of concurrent chemoradiation or radiation (mid-EBV DNA) was prognostic of a worse PFS and OS (9).…”
Section: Discussionmentioning
confidence: 99%